Choroidal vascularity index: a step towards software as a medical device. Issue 2 (29th January 2021) - Betzler, Bjorn Kaijun; Ding, Jianbin; Wei, Xin; Lee, Jia Min; Grewal, Dilraj S; Fekrat, Sharon; Sadda, Srinivas R; Zarbin, Marco A; Agarwal, Aniruddha; Gupta, Vishali; Schmetterer, Leopold; Agrawal, Rupesh
Abstract : The choroidal vascularity index (CVI) is a relatively new parameter, calculated off optical coherence tomography (OCT) images, for the quantitative evaluation of choroid vascularity. It is defined as the ratio of vascular area to the total choroidal area, presented as a percentage. The choroid is an important vascular bed, often implicated in ocular and systemic conditions. Since the introduction of CVI, multiple studies have evaluated its efficacy as a tool for disease prognostication and monitoring progression, with promising results. The CVI was born out of the need for more robust and accurate evaluations of choroidal vasculature, as prior parameters such as choroidal thickness and choroidal vessel diameter had their limitations. In this review, we summarise current literature on the CVI, explain how the CVI is derived and explore its potential integration into future research and translation into clinical care. This includes the application of CVI in various disease states, and ongoing attempts to produce an automated algorithm which can calculate CVI from OCT images.